2018
DOI: 10.1016/j.bja.2017.11.075
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a new dual channel laryngeal mask airway, the LMA®Gastro™ Airway, for upper gastrointestinal endoscopy: a prospective observational study

Abstract: ACTRN12616001464459.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 35 publications
(27 reference statements)
1
35
1
3
Order By: Relevance
“…The main adverse effect in our study was a relatively high presence of blood staining after LMA removal, observed in 70 (25%) patients, in comparison with no cases in Sng's study and three cases (6%) in Moser's report . A recent report with a new silicone SAD, the LMA Gastro TM airway, which shares some features with the LMA Protector, reported the presence of blood staining in 76% of 292 patients . The incidence of blood staining after SAD removal ranges between 0% and 50%, and is related to differences in difficulty of insertion, provider experience and patient characteristics .…”
Section: Discussioncontrasting
confidence: 56%
“…The main adverse effect in our study was a relatively high presence of blood staining after LMA removal, observed in 70 (25%) patients, in comparison with no cases in Sng's study and three cases (6%) in Moser's report . A recent report with a new silicone SAD, the LMA Gastro TM airway, which shares some features with the LMA Protector, reported the presence of blood staining in 76% of 292 patients . The incidence of blood staining after SAD removal ranges between 0% and 50%, and is related to differences in difficulty of insertion, provider experience and patient characteristics .…”
Section: Discussioncontrasting
confidence: 56%
“…17,18 Previous studies have demonstrated the efficacy of the LG during upper GI endoscopy in the adult population, but this is the first study evaluating its use in a cohort of pediatricaged patients. 19,20 The principal findings of this prospective study, comparing the clinical outcomes of two types of SGDs, were that the LG was easy to use with limited instruction, limited the increase in intracuff pressure from baseline, and slightly improved the ease of the procedure. However, we noted no difference in the primary outcome of the study, which was the change of intracuff pressure of the SGDs.…”
Section: Discussionmentioning
confidence: 97%
“…This particular SAD already has proven efficacy in upper gastrointestinal endoscopy procedures. 6 We report the successful insertion of a TEE probe in the channel for esophageal intubation of the LMA Gastro in 9 patients undergoing percutaneous patent foramen ovale (PFO) closures, a short procedure done with increasing relevance and frequency. [7][8][9][10][11][12] Written informed consent was obtained from patients.…”
Section: To the Editormentioning
confidence: 99%